The Effectiveness of Chest Physiotherapy for Pneumonia Patients with Ineffective Airway Clearance Problems in Intensive Care Unit - Arifin, Nadilla Ayu; Yunanto, Rismawan Adi; Ridla, Akhmad Zainur; Siswanto, Heri (Jurnal Kegawatdaruratan Medis Indonesia, 2024)
In patients with decreased consciousness and a respirator installed in intensive care unit room, it causes obstruction to discharge of secretions. Excessive accumulation of secretions in the airways can obstruct the airways and cause the patient to experience dyspnea. These conditions can cause ineffective airway hygiene problems. Ineffective airway clearance problems may occur in patients with pneumonia caused by excessive accumulation of secretions. The purpose of this studi was to determine the effectiveness of implementing chest physiotherapy interventions in overcoming the problem of ineffective airway clearance nursing in patients in the ICU. Case study with a nursing care approach to patients in the intensive care unit. The sample used was 1 patient with chest physiotherapy nursing intervention for 3x24 hours in the form of chest physiotherapy. The results showed that effectiveness of implementing chest physiotherapy interventions in overcoming the problem of ineffective airway clearance nursing in patients in the ICU which is carried out in two sessions each shift is effective for reducing additional rhonchi breath sounds, reducing respiratory frequency, and helping to remove secretions. Based on the results, researcher conclude that nursing care for patients with ineffective airway clearance problems can be resolved with chest physiotherapy.